2019
DOI: 10.1371/journal.pone.0216135
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide research trends on aristolochic acids (1957–2017): Suggestions for researchers

Abstract: Aristolochic acids and their derivatives are components of many traditional medicines that have been used for thousands of years, particularly in Asian countries. To study the trends of research into aristolochic acids and provide suggestions for future study, we performed the following work. In this paper, we performed a bibliometric analysis using CiteSpace and HistCite software. We reviewed the three phases of the development of aristolochic acids by using bibliometrics. In addition, we performed a longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 96 publications
0
21
0
Order By: Relevance
“…Subsequently, Balkan endemic nephropathy (BEN) has also been found to be associated with the exposure to AAs. Since then, different studies have addressed the characterization and quantitation of AA analogs in plants and products, and the underlying mechanisms involved in the adverse reactions of AAs have been broadly described (Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Balkan endemic nephropathy (BEN) has also been found to be associated with the exposure to AAs. Since then, different studies have addressed the characterization and quantitation of AA analogs in plants and products, and the underlying mechanisms involved in the adverse reactions of AAs have been broadly described (Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first bibliometric study to analyze and quantify global research productivity related to AAN. However, it should be mentioned that Zhang et al recently published a bibliometric analysis and systematic review of global publications regarding trends in AAs, [ 3 ] whereas our study included only publications pertaining to AAN.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 , 2 ] Although botanicals that are known or suspected to contain AAs are no longer permitted in many countries, the incidence of AAN is probably much higher than initially thought, particularly in Asia. [ 3 ] In Asian countries, especially China, traditional medicines for self-medication or agricultural products sold by networks have become a trend. Owing to a similar pronunciation, AA-containing herbs are always misused for “ mutong ” or “ fangchi ,” which belong to Akebia Decne genus and Menispermaceae family, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately however, the studies did not include tumour histopathology. Recently published bibliographic analysis of research trends on aristolochic acids [28] has also concluded that 'there is insufficient epidemiological and animal experimental evidence to support a direct correlation between the mutational signature of AA and cancer'.…”
Section: Discussionmentioning
confidence: 99%